BIO-ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF AVELUMAB, AXITINIB AND ITS APPLICATION TO PHARMACOKINETIC STUDIES IN RABBIT PLASMA BY USING LCMS/MS - RAFI, SYED; RAMBABU, KANTIPUDI (International Journal of Applied Pharmaceutics, 2021)
Objective: An easy, quick, precise, active and reproducible LC-MS/MS technique was developed for the bioanalytical method of Avelumab and Axitinib using Cytarabine as an internal standard. Methods: This article summarizes the recent progress on bioanalytical LC-MS/MS methods using waters x-bridge phenyl column (150x4.6 mm, 3.5µ) column and organic mobile phase of 0.1% Tri fluoro acetic acid and Acetonitrile in 50:50 ratio. Results: The calibration curve was linear in the range of 2-40 ng/ml for avelumab and 0.5-10 ng/ml axitnib. Accuracy, precision, recovery, matrix effect and stability results were found to be within the suitable limits. Simple and efficient method was developed and utilized in pharmacokinetic studies to see the investigated analyte in body fluids. Conclusion: The application denotes all the parameters of system suitability, specificity, linearity and accuracy are in good agreement with USFDA guidelines and applied effectively for the investigation of pharmacokinetic studies in rabbit.